Phytochemical Profiling of Ephedra alata subsp. alenda Seeds by High-Performance Liquid Chromatography-Electrospray Ionization-Quadrupole-Time-of-Flight-Mass Spectrometry (HPLC-ESI-QTOF-MS), Molecular Docking, and Antioxidant, Anti-diabetic, and Acetylcholinesterase Inhibition - Mufti, Afoua; Tir, Meriam; Zarei, Armin; Contreras, María del Mar; Gómez-Cruz, Irene; Feriani, Anouar; Ghazouani, Lakhdar; Saadaoui, Ezzeddine; Allagui, Mohamed Salah; Harrath, Abdel Halim; Ramazani, Ali; Tlili, Nizar (Analytical letters, 2022)
The aim of the current work was to study for the first time the phytochemical profile of Ephedra alata subsp. alenda seeds extract (ESS). The extract was characterized using high-performance liquid chromatography coupled to electrospray ionization quadropole time-of-flight mass spectrometry (HPLC-ESI-QTOF/MS). The antioxidant and antihemolytic properties were evaluated, and the inhibitory properties against α-amylase, α-glucosidase, and acetylcholinesterase were assessed. Chromatographic analysis revealed that ESS was rich in bioactive components including ephedrine derivatives, sphingolipides, flavonol, hexoside, and fatty acids. Furthermore, ESS displayed important antioxidant activity and α-glucosidase, α-amylase, and acetylcholinesterase inhibitory capacities. Moreover, ESS showed a preventive effect against oxidative stress induced hemolysis. In silico analysis confirmed the beneficial effects of ESS-phytochemicals. In fact, 3 out of the 14 investigated compounds, including isorhamnetin rutinoside, isoschaftoside, and kaempferol-3-rhamnoside, exhibited the best binding scores (less than −7) with two anti-diabetic targets. Isorhamnetin rutinoside also showed the highest number of hydrogen bonds with acetylcholinesterase highlighting its anti-cholieaterase potency. The current study suggested that seeds from E. alata are interesting sources of bioactive compounds and recommended as enzyme inhibitory agents in food and pharmaceuticals.